Exploration about Beliefs of God through Cordiality of the Good Samaritan Parable and Homoousios of Nicaea Council - Xalastinus Jasper Hanta; Samuel Pella (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2025)
Discussing the Parable of the Good Samaritan, one of the main themes that can be discussed is the theology of cordiality "his heart was moved with compassion". This cordiality is revealed from the actions of the Good Samaritan figure. He helped a victim who needed a helping hand of compassion. Insinuatingly, the actions of the good Samaritan were driven by his cordiality. In the context of the Council of Nicaea, the beliefs about God are summarized in homoousios. The beliefs about God in Jesus are as follows: God who is one in essence and God who is in cordial with human being. This article will discuss the beliefs or spirituality derived from a combined analysis of the cordiality of the Good Samaritan and the concept of homoousios in the Council of Nicaea. The author uses historical-critical analysis and hermeneutic methods. These methods were carried out using library research. From the cordial actions of the Good Samaritan and the concept of homoousios, the author finds concepts and relevancies: Almighty God transcends the limits of human being; but also, Almighty God become human being and moves humans to do cordial acts of love specifically for the marginalized and suffering.